Student Perceptions of Zotero as a Reference Management Tool: Barriers, Handling, and Sustainability of Use - Cici Sri Rezaki Sastrani; Mariyadi; Ahmad Rabiul Muzammil (LPPM Undiksha, 2026)
The rapid advancement of digital technology has increased the demand for university students to manage academic references effectively, systematically, and accurately. Nevertheless, the use of digital reference management applications continues to present several technical and operational challenges. This study aims to develop a model of students’ perceptions regarding the use of Zotero as a digital reference management tool by examining their experiences, encountered challenges, coping strategies, and continued use. A qualitative approach employing a phenomenological design was adopted to obtain an in-depth understanding of users’ experiences. Data were collected through semi-structured interviews with students at Tanjungpura University in 2025 who had experience using Zotero for academic purposes. The data were analyzed using thematic analysis involving coding, categorization, and the identification of overarching themes. The findings revealed three major themes: barriers to use, coping strategies, and continuity of use. The identified barriers included integration problems with word-processing software, incomplete metadata, and inaccurate ISBN and DOI entries. Students addressed these challenges through training, peer assistance, independent exploration, and online tutorials. Despite these difficulties, students continued to use Zotero because of its perceived benefits in improving reference management efficiency, citation accuracy, and organizational consistency. The findings underscore the importance of developing innovative training strategies and providing sustained academic support to strengthen students’ digital literacy and foster an effective, autonomous, and sustainable digital academic ecosystem in higher education.